PENERAPAN METODE PIECES DALAM PENGEMBANGAN SISTEM INFORMASI MANAJEMEN TUGAS AKHIR (STUDI KASUS : PRODI SISTEM INFORMASI UNIYAP) - Salahudin Robo; Sitti Nur Alam; Teguh Dwi Julianto (Jurnal Tekno Kompak, 2021)
Information Systems study program is one of the study program at the Yapis University of Papua. One of its academic activities, the processing of the Final Project, has not utilized technology optimally which the collection of final project documents are still in print out. This becomes problems faced by study program administrations such as limited storage space, damage and loss of documents, besides that the costs incurred by students are quite large for printing documents. The purpose of this study is to create an integrated final project management system so that it can facilitate the work of all parties that are directly related to student final project management. The analysis method used in this research is the PIECES method, the UML method as the system design, the waterfall as the development method and the Black box testing method used as testing method. For the data collection process, this research uses interview, observation and literature study techniques. The result of this research is a Final Project Management Information System which aims to make easier for students in managing their Final Projects and for facilitate the study program in managing student Final Projects